Mobile phone use amongst students in a university in Malaysia: its correlates and relationship to psychological health - Zulkefly, Nor Sheereen; Baharudin, Rozumah (EuroJournals Publishing, 2009)
The study explored the extent of mobile phone use amongst students of Universiti Putra Malaysia. Additionally, the study determined personal and family factors related to the mobile phone use and, the relationship between problem mobile phone use and psychological health of the students. The multi-stage cluster sampling was employed to identify the students (N=386) who completed a self-administered questionnaire. The students were found to spend on average 6 hours daily and USD18.70 monthly on their mobiles. Text message was the most used feature and peers were the most frequently contacted person. Older students used more voice calls while females text message more frequently. Male and younger students were more interested with other features (MMS and GPRS) of the mobiles. Students from higher income families spent more time and money on their mobile phone. Additional analyses showed that students with lower self-esteem and spent more time on the phone were more likely to be problem phone users. Adolescents who spend more time on their mobile phone were also more vulnerable to psychological disturbances. There is a need to further uncover underlying factors that influence students' mobile phone behavior, and the consequences of intense mobile phone use on their psychological well-being.